Effects of acute tryptophan depletion on raphé functional connectivity in depression. Issue 2 (30th November 2015) - Weinstein, Jodi J.; Rogers, Baxter P.; Taylor, Warren D.; Boyd, Brian D.; Cowan, Ronald L.; Shelton, K. Maureen; Salomon, Ronald M.
Abstract: Depression remains a great societal burden and a major treatment challenge. Most antidepressant medications target serotonergic raphé nuclei. Acute tryptophan depletion (ATD) modulates serotonin function. To better understand the raphé's role in mood networks, we studied raphé functional connectivity in depression. Fifteen depressed patients were treated with sertraline for 12 weeks and scanned during ATD and sham conditions. Based on our previous findings in a separate cohort, resting state MRI functional connectivity between raphé and other depression-related regions (ROIs) was analyzed in narrow frequency bands. ATD decreased raphé functional connectivity with the bilateral thalamus within 0.025–0.05 Hz, and also decreased raphé functional connectivity with the right pregenual anterior cingulate cortex within 0.05–0.1 Hz. Using the control broadband filter 0.01–0.1 Hz, no significant differences in raphé-ROI functional connectivity were observed. Post-hoc analysis by remission status suggested increased raphé functional connectivity with left pregenual anterior cingulate cortex in remitters ( n =10) and decreased raphé functional connectivity with left thalamus in non-remitters ( n =5), both within 0.025–0.05 Hz. Reducing serotonin function appears to alter coordination of these mood-related networks in specific, low frequency ranges. For examination of effects of reduced serotonin function on mood-related networks, specific low frequency BOLD fMRI signals can identify regions implicated in neural circuitry and may enable clinically-relevant interpretation of functional connectivity measures. The biological significance of these low frequency signals detected in the raphé merits further study. Highlights: Functional connectivity of the serotonergic pontine raphé is modeled in depression. We gave acute tryptophan depletion (ATD) or sham diets during resting state fMRI. ATD altered raphé functional connectivity with regions involved in depression. Specific changes were detected in narrowly-defined frequency ranges. Changes in raphé function can be detected using resting fMRI.